Microhematuria Enhances the Risks of Relapse and Renal Progression in Primary Membranous Nephropathy - He, Peng; Yu, Xiaoyong; Zha, Yang; Liu, Jing; Wang, Hanmin; Huang, Chen; Sun, Shiren; He, Lijie (Frontiers in Medicine, 2021)
Abstract Objective: To determine whether there is an association between microhematuria and relapse or kidney disease progression in patients with primary membranous nephropathy (PMN). Methods: A cohort of 639 patients with biopsy-proven PMN from two centers was followed for a median of 40 months. The exposures were initial hematuria, time-averaged hematuria, and cumulative duration of hematuria. The outcomes were relapse and renal progression, which were defined by a 40% reduction in renal function or end-stage renal disease. Cox proportional hazards regression and competing risk analyses were performed to yield hazard ratios (HRs) and subdistribution hazard ratios (sHRs) with 95% confidence intervals (CIs). Sensitivity and interaction analyses were also performed. Results: After adjusting for confounders, a higher level of initial hematuria was associated with a 1.43 (95% CI, 1.15-1.78) greater hazard of relapse. Worsening hematuria remarkably increased the risk of short-term relapse (HR, 3.93; 2.82-5.47). Time-averaged hematuria (sHR, 1.35; 1.12-1.63) and cumulative duration of hematuria (sHR, 1.17; 1.02-1.34) were independent predictors of renal progression. Hematuria remission was related to a reduced risk of renal progression over time in patients with positive microhematuria (sHR, 0.63; 0.41-0.96). Conclusions: A higher level of initial hematuria was a remarkable predictor of relapse in patients with PMN, and the magnitude and persistence of microhematuria were independently associated with kidney disease progression. Keywords: Primary membranous nephropathy, Microscopic hematuria, Relapse, Kidney disease progression, Remission